Constructing Transparency in the Car Transportation Sector - Federico Zaupa (Iperstoria)
In addition to its common definition as the act of openly sharing information, ‘transparency’ has been defined in various ways, namely as information ‘disclosure,’ ‘completeness,’ ‘accuracy,’ ‘clarity,’ ‘availability,’ and ‘visibility.’ Research in Corporate Social Responsibility (CSR) communication has highlighted the impact of ‘transparency’ on the trust attitudes of stakeholders. Despite the importance of this issue, no linguistic research on CSR disclosures has focused on the discursive construction of the concept of ‘transparency.’ To fill this gap, this research uses the car rental and ride sharing sectors as a case study and analyses a corpus of CSR/ESG reports and news releases published by companies operating in these fields of transportation, combining quantitative and qualitative methods of corpus-based discourse analysis. The results suggest that ‘transparency’ is presented as an ethical value and a tool ensuring accountability, understandability and fairness. In relation to the strategies used to communicate the companies’ approach to ‘transparency,’ the data reveal a plethora of commissive statements, through which they demonstrate their commitment to this issue. Finally, the frequent use of quality assessment verbs or adjectives, nouns with generic use, and vague expressions of degree, suggest that the concept of ‘transparency’ assumes a vague meaning in CSR disclosures.